2021
DOI: 10.1093/ons/opab170
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Advanced Age on Clinical Outcomes After Vestibular Schwannoma Resection in the Very Elderly: Cohort Study

Abstract: BACKGROUND Vestibular schwannomas (VS) have a peak incidence in the sixth and seventh decades of life. Stereotactic radiosurgery is often the preferred treatment for VS among patients of advanced age. The fraction of elderly patients potentially requiring consideration for surgical treatment is anticipated to expand, mandating an update to management paradigms in this population. OBJECTIVE To describe our experience with surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
14
2
Order By: Relevance
“…The analysis found that the frail group had statistically significant higher rates of readmission, postoperative infection, facial paralysis, urinary tract infection, and hydrocephalus [ 75 ]. If elderly patients are more prone to develop general complications after surgery (including acute cardiac events, stroke, bleeding, postoperative delirium, prolonged inpatient stays as well as mortality), complications specific to VS and its removal, including cerebrospinal fluid leak or FN dysfunction, were not shown to be significantly higher, as shown on a population of 452 patients divided by age cutoff > 70 years [ 76 , 77 ]. sRS results proved particularly favorable in elderly patients in terms of overall outcome and reliable tumor control.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis found that the frail group had statistically significant higher rates of readmission, postoperative infection, facial paralysis, urinary tract infection, and hydrocephalus [ 75 ]. If elderly patients are more prone to develop general complications after surgery (including acute cardiac events, stroke, bleeding, postoperative delirium, prolonged inpatient stays as well as mortality), complications specific to VS and its removal, including cerebrospinal fluid leak or FN dysfunction, were not shown to be significantly higher, as shown on a population of 452 patients divided by age cutoff > 70 years [ 76 , 77 ]. sRS results proved particularly favorable in elderly patients in terms of overall outcome and reliable tumor control.…”
Section: Resultsmentioning
confidence: 99%
“…The middle fossa approach, usually preferred in small intrameatal tumors, was used once, since most of these were nongrowing and many of the patients had stable hearing with 100% discrimination score. Studies also comment that radiotherapy often is a consideration in this group . While stereotactic radiosurgery (SRS) worldwide may be a more frequently used treatment modality in the older adult population with increased complication risk, it was not a popular treatment modality in Denmark in the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Only 10 patients with a growing VS in Denmark (3 of whom had previous VS surgery) were treated with radiation treatment in the study period, and the group was, for that reason, excluded from the study; however, it would be logical to count in the SRS group as well. Studies have reported SRS to be an appealing option due to its capability to diminish tumor growth, minimal threat to the facial nerve, and lower risk of hearing loss, and underline furthermore that comorbidities and dizziness are prevalent in older adult patients, yet no significant differences exist after surgery in hard parameters, such as facial nerve weakness, hearing impairment, or general surgical complications . Furthermore, regarding radiotherapy, gamma knife is not an option in Copenhagen, and the aforementioned patients received conventional fractionated or hypofractionated stereotactic radiotherapy, which timewise obviously is inferior to the onetime gamma knife treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations